Analisis Strategi Pengembangan Produksi Anggrek Dendrobium di Grenpace Kota Tangerang Selatan - Prayudi, Anselmus Abimayung; Setiyawan, Hery; Budiraharjo, Kustopo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study analyzes the internal and external factors that influence the production of Dendrobium orchid seedlings and provides strategic recommendations to address these challenges. The SWOT analysis is applied to identify the strengths, weaknesses, opportunities, and threats affecting production and partnerships. Quantitative data from the IFE and EFE matrices are then used to determine the company’s strategic position through the IE matrix. Based on this position, the QSPM method helps formulate and prioritize the most effective and efficient production strategies. The results indicate that PT Grenpace possesses strengths in tissue culture technology mastery, high product quality, and an extensive plasma partnership network. The company, however, faces several weaknesses such as dependence on plasma partners, high production costs, and limited promotion activities. External opportunities that can be leveraged include government support for the agribusiness sector, increasing trends in ornamental plant demand, and potential export markets. Nonetheless, the company also faces threats from business competition, regulatory changes, and dependence on skilled labor. Through the IFE and EFE matrix analysis, scores of 3.90 and 3.50 were obtained, indicating that the company is positioned in quadrant 1 of the IE matrix, categorized as the “grow and build” position. The prioritized strategy is the SO strategy, which utilizes the company’s strengths to seize market opportunities. The formulated strategies include strengthening marketing and technology-based market expansion, optimizing government support for funding and program access, and developing innovative products along with expanded distribution. Based on the QSPM matrix calculation, the strategy of strengthening marketing and technology-based market expansion was selected as the top priority, with the highest Total Attractiveness Score (TAS) of 5.607. This strategy is considered the most suitable to support PT Grenpace’s long-term growth and competitiveness.